ANALISIS KEMAMPUAN KERJA SUPPY CHAIN MANAGEMENT PADA KFC (STUDI KASUS PADA ACEH FRIED CHICKEN DI DELI SERDANG) - Wulandari, Ayu; Maha, Nurita; Aisyah, Siti (Yana Research, 2023)
Penelitian ini penting untuk mengetahui supply chain management yang berkaitan dengan persediaan bahan baku khusunya pada industri makanan di UMKM kecil. Tujuannya untuk memahami supply chain management terhadap pengadaan bahan baku. Dalam metode penelitian kualitatif ini, populasi dan sampel dalam penelitian yang didapatkan adalah yang mana disebutkan sebagai dengan responden. Dalam metode penelitian kualitatif ini, sampel dan populasi pada penelitian didapatkan ialah yang mana disebutkan sebagai dengan responden. Kemudian teknik pengumpulan data dalam penelitian kualitatif ialah dengan wawancara. Yang menjadi objek dalam penelitian ini ialah responden pihak SCM Aceh Fried Chicken (AFC) di Deli serdang. Supply chain management ini berpengaruh terhadap persediaan bahan baku. ABSTRACT This research is important to know supply chain management related to raw material inventory, especially in the food industry in small UMKM. The goal is to understand supply chain management for the procurement of raw materials. In this qualitative research method, the population and sample in the study obtained are those who are mentioned as respondents. In this qualitative research method, the sample and population in the study were found to find which one was mentioned as the respondent. Then the data collection technique in qualitative research is by interviewing. The object of this research is the respondent from SCM Aceh Fried Chicken (AFC) in Deli Serdang. This supply chain management hasan effect on avery adequate supply of raw materials and good quality with excellent supply chain management will obtain asupply of raw materials and can meet the needs and demands needed at Aceh Fried Chicken in Deli Serdang. The AFC needs to continue to improve the management or governance of the UMKM supply chain so that raw materials are always sufficient and available whenever needed.